The Pivotal Role of Management Control in Times of Crisis: Enhancing Organizational Resilience and Strategic Adaptation - Nabila Snoussi; Azzouz Elhamma (European Scientific Journal, ESJ, 2024)
This article examines the transformation of management control, which has traditionally been regarded as a support function, into a central strategic lever in times of crisis. The study is centred on three core areas of enquiry: the impact of management control mechanisms on organisational performance; their role in facilitating adaptation in a crisis context; and the influence of the adoption of new control tools on the company's strategic direction. The research, based on a quantitative study of 97 companies, demonstrates that management control is a key factor in enhancing performance, organisational resilience and the implementation of a proactive strategy. The findings indicate that the integration of advanced technologies, such as artificial intelligence and ERP, enables companies to anticipate risks and capitalise on opportunities, thereby strengthening their competitive advantage in times of crisis. However, several limitations remain. These include the relatively small sample size, the specific nature of the crises under study, and the potential for bias in respondents' perceptions. These factors highlight the need for further research, particularly the exploration of additional crisis contexts and the use of mixed methodologies for a more comprehensive analysis.